Pharmacological Human Enhancement: An Overview of the Looming Bioethical and Regulatory Challenges - Ricci, Giovanna (Frontiers in Psychiatry, 2020)
Cognitive enhancement, a rather broad-ranging principle, can be achieved in various ways: healthy eating and consistent physical exercise can lead to long-term improvements in many cognitive domains; commonplace stimulants such as caffeine, on the other hand, temporarily raise levels of alertness, attentiveness and concentration; sedative substances are also used as an indirect form of enhancement to relax before an exam or an important meeting. Such approaches raise no ethical issue. Nonetheless, clinical research has led to the off-label use of drugs called nootropics or “smart drugs”, which can, under certain conditions, elicit some degree of cognition-improving effects: methylphenidate and modafinil can enhance working memory and concentration in healthy individuals, although the significance and effectiveness of such applications are dubious. Such “cognitive enhancement” methods, however, do raise multiple ethical issues, and their contentious nature has caused bioethical authorities to lay out opinions and recommendations meant to regulate their use. Most notably, the Italian Committee on Bioethics has extensively dealt with the spread of nootropics, which resulted in the Italian Code of Medical Ethics including “cognitive enhancement” drugs and their prescription by doctors as critical points, along with cosmetic surgery (the latest version of the Code, updated in December 2017, deals with the two separately, in Article 76 and 76 BIS). The United States Presidential Commission for the Study of Bioethical Issues broadened the scope of cognitive enhancement techniques so as to include neural modifiers, i.e. mechanisms of brain and nervous system change: a much wider array of interventions, technologies, behaviours and environmental conditions that may potentially affect several aspects of the human brain and nervous system. The potential of neuroscience to profoundly reshape society is nothing short of mind-blowing.